SUCCESSFUL MANAGEMENT OF CANINE ATOPIC DERMATITIS USING OCLACITINIB - A CASE REPORT - Navjot Singh Thakur; M.A. Ensha Lomiya; R. Raguvaran; Umesh Dimri; Vivek Joshi; D.B. Mondal; K. Kavitha; Akhilesh Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A Dalmatian dog -was brought to the Referral Veterinary Polyclinic, ICAR- Indian Veterinary Research Institute, Izatnagar with a complaint of erythematous lesions, alopecia and intense itching and had been treated for a long time. Atopic dermatitis was diagnosed based on the history and the exclusion of other infectious agents as potential causes of the dermatitis. The dog was treated with oclacitinib, antibacterial, fatty acids and antihistaminic medications and showed remarkable improvement after therapy.